Involving consumers and the community in the development of a diagnostic instrument for fetal alcohol spectrum disorders in Australia - Jones, Heather M (BioMed Central, 2013)
BACKGROUND: Australia’s commitment to consumer and community participation in health and medical research has grown over the past decade. Participatory research models of engagement are the most empowering for consumers. METHODS: As part of a project to develop a diagnostic instrument for fetal alcohol spectrum disorders (FASD) in Australia (FASD Project), the Australian FASD Collaboration (Collaboration), including a consumer advocate and two consumer representatives, was established. On completion of the FASD Project an on-line survey of Collaboration members was conducted to assess their views on consumer involvement. Women in the community were also invited to participate in Community Conversations to discuss real life situations regarding communications with health professionals about alcohol and pregnancy. Community Conversation feedback was analysed qualitatively and attendees were surveyed about their views of the Community Conversation process. RESULTS: The on-line survey was completed by 12 members of the Collaboration (71%). Consumer and community participation was considered important and essential, worked well, and was integral to the success of the project. The 32 women attending the Community Conversations generated 500 statements that made reference to prevention, how information and messages are delivered, and appropriate support for women. Nearly all the attendees at the Community Conversations (93%) believed that they had an opportunity to put forward their ideas and 96% viewed the Community Conversations as a positive experience. CONCLUSIONS: The successful involvement of consumers and the community in the FASD Project can be attributed to active consumer and community participation, which included continued involvement throughout the project, funding of participation activities, and an understanding of the various contributions by the Collaboration members.